Web semântica: aspectos interdisciplinares da gestão de recursos informacionais no âmbito da ciência da informação - Ramalho, Rogério Aparecido Sá [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
In the scope of the information resource management, the models and methods of organization and retrieval of information were always conditioned to the used technologies, so that with the development and intensification of digital technology uses, a new scale of possibilities has been incorporated to the production process, storage, representation and retrieval of information, reaching a stage where the classic models of organization and retrieval of information need to be (re)thought under different perspectives, because they don t seem to be able to solve the problems identified in the Web environment, becoming evident the need of development of new technologies that allow to optimize the retrieval of information in digital environment. In this way, the studies related to the Semantic Web project have been detaching as a new perspective in the development of technologies that enable an increase in the quality and relevance of the recovered information through the development of instruments that allow describing them formally, in a format that can be processed by machines. The semantic aspects that are inherent to the information resources contribute to the identification and contextualization of the available information in the Web environment. In this way, the proposition of this research is the accomplishment of a theoretical and methodological study of interdisciplinary characteristic about the Semantic Web project, aiming to identify its theoretical basis, favoring the demystification of the concepts and subjacent technologies, and evaluating in what stage the Information Science area can contribute to its concretization, becoming evident the possible reflexes of these new technological approaches in its theoretical corpus. So a bibliographic review about the development of the Internet and the main concepts and technologies inherent to the Web Semantic... (Complete abstract, click electronic address below)

No âmbito da gestão de recursos informacionais os modelos e métodos de organização e recuperação de informações sempre estiveram condicionados às tecnologias utilizadas, de modo que com desenvolvimento e intensificação da utilização das tecnologias digitais uma nova gama de possibilidades vem sendo incorporada aos processos de produção, armazenamento, representação e recuperação de informações, atingindo um estágio em que os modelos clássicos de organização e recuperação de informações precisam ser (re)pensados sob diferentes perspectivas, pois os mesmos não parecem ser capazes de solucionar os problemas identificados no ambiente Web, evidenciando a necessidade de desenvolvimento de novas tecnologias que permitam otimizar a recuperação de informações em ambientes digitais. Nesse sentido, os estudos relacionados ao projeto Web Semântica vêm destacando-se como uma nova perspectiva no desenvolvimento de tecnologias que possibilitem um aumento na qualidade e relevância das informações recuperadas, a partir do desenvolvimento de instrumentos que permitam descrever formalmente, em um formato que possa ser processado por máquinas, os aspectos semânticos inerentes aos recursos informacionais, contribuindo para a identificação e contextualização das informações disponíveis no ambiente Web. Deste modo, a proposição deste trabalho é a realização de um estudo teórico e metodológico de caráter interdisciplinar acerca do projeto Web Semântica, buscando favorecer a desmistificação dos conceitos e tecnologias subjacentes e avaliar em que medida a área de Ciência da Informação pode contribuir para sua concretização, ressaltando os possíveis reflexos destas novas abordagens tecnológicas em seu corpus teórico. Assim, apresenta-se um levantamento bibliográfico acerca do desenvolvimento da Internet...
Keywords: Recuperação da informação; Ontologia; Gerenciamento de recursos de informação; Internet; Redes de computadores; Web semântica; Semantic Web Internet; Ontology; Information Retrieval; Information Resources Management; Internet